2021
DOI: 10.2215/cjn.19801220
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in the Modern Era of Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Background and objectives Acute kidney injury (AKI) is a major complication of allogeneic hematopoietic stem cell transplantation, increasing risk of non-relapse mortality. AKI etiology is often ambiguous due to heterogeneity of conditioning/graft-versus-host disease (GVHD) regimens. To date, GVHD and calcineurin inhibitor effects on AKI are not well defined. We aimed to describe AKI and assess pre/post-hematopoietic transplant risk factors in a large recent cohort. Design, setting, participants, and measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…Factors known to contribute to the risk of AKI after HCT include pre-treatment factors such as being female ( 21 ), age 55 years or older ( 22 ), and underlying conditions such as diabetes ( 23 ), hypertension ( 21 ), and chronic kidney disease (CKD) ( 24 ). Risk factors for AKI associated with HCT include TBI conditioning ( 22 ), use of a calcineurin inhibitors (CNIs) for GVHD prevention ( 23 , 25 , 26 ), and use of MTX for GVHD prophylaxis ( 22 , 23 ). Post-transplant stay in an intensive care unit ( 21 ) and the need for mechanical ventilation ( 27 ) are also risk factors.…”
Section: Kidney Disease After Hctmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors known to contribute to the risk of AKI after HCT include pre-treatment factors such as being female ( 21 ), age 55 years or older ( 22 ), and underlying conditions such as diabetes ( 23 ), hypertension ( 21 ), and chronic kidney disease (CKD) ( 24 ). Risk factors for AKI associated with HCT include TBI conditioning ( 22 ), use of a calcineurin inhibitors (CNIs) for GVHD prevention ( 23 , 25 , 26 ), and use of MTX for GVHD prophylaxis ( 22 , 23 ). Post-transplant stay in an intensive care unit ( 21 ) and the need for mechanical ventilation ( 27 ) are also risk factors.…”
Section: Kidney Disease After Hctmentioning
confidence: 99%
“…Most of the renal injury after HCT is thought to be caused by nephrotoxic drugs, particularly CNIs given for GVHD prophylaxis ( 34 ). CNIs can cause both AKI and CKD ( 61 ); however, CNIs serum concentration does not always correlate with the severity of AKI ( 26 ). CNIs cause AKI through a variety of mechanisms.…”
Section: Etiologies Of Aki After Hctmentioning
confidence: 99%
“…Although the prognosis of patients undergoing HSCT has improved in recent years, a meta-analysis of 36 cohort studies found that AKI incidence after HSCT remained high throughout the years, affecting more than half of the patients [ 3 ]. As such, a proper assessment of the risk factors associated with AKI occurrence in the HSCT population is of extreme importance, since HSCT patients’ prognosis may be additionally improved by addressing the modifiable ones.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies approached the subject of AKI following HSCT, most of them were performed in a retrospective manner [ 3 , 4 , 5 ]. As well, the literature provides inconsistent evidence on the relationship between AKI and calcineurin inhibitors (CNI) overdosing [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the severity of renal failure increases, the mortality rate of AKI patients also increases, accounting for more than 80% of patients requiring RRT 5 . The incidence of non-recurring deaths in AKI patients is high (HR 2.77, 95% CI 1.8–4.27) 6 . The study found that the cumulative mortality rate of the non-malignant disease AKI group within 100 days after HSCT was significantly higher than that of the non-AKI group (44.4% vs. 0%, p = 0.003) 7 .…”
Section: Introductionmentioning
confidence: 99%